ETHNOCULTURAL CONNECTION OF THE KYRGYZ WITH THE ALTAI PEOPLES (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
As a result of the world globalization process in the modern world, many peoplesare losing their specific features, regional cultural differences. This situation raises interethnic,interfaith relations to the forefront in most regions of the world. With the wave of democratizationand independence, international relations have become complicated and the geopolitical picturein Central Asia has changed. In this regard, the study of the history of ethnopolitical and culturalrelations of this or that nation is an overriding task facing scientists. Today, in the context of theaggravation of the national question, the study of the history of relations between peoples is veryrelevant, since many works have appeared in which the historical process is distorted in favorof nationalist aspirations, the exclusiveness of individual nations or ethnic groups is artificiallypromoted, and sometimes the role and place in the history of this or that people is deliberatelyunderestimated.
Keywords: confederation, ethnopolitics, cultural relations, Central Asia, Turkic peoples.